The Impact of Environmental, Social, and Governance Disclosure on Firm Value of Energy Sector Companies - Cici Wulan Syanggraini; Erna Sulistyowati (FEBI IAIN Langsa, 2026)
This study aims to analyze the effect of environmental, social, and governance disclosure on the company value of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Company value in this study is measured using Tobin’s Q. Environmental, Social, and Governance Disclosure is measured based on GRI Standards indicators, which consist of 32 environmental indicators, 36 social indicators, and 13 governance indicators. The study uses a quantitative approach with purposive sampling, consisting of 55 energy sector companies. Secondary data taken from annual reports and sustainability reports available on the IDX website or company websites. Panel data analysis with statistical testing was conducted using EViews 12 software. The research results show that Environmental disclosure does not have a significant effect on firm value, indicating that investors in the Indonesian capital market have not fully factored environmental disclosure information into their investment decisions. Social disclosure has a significant negative effect on firm value, suggesting that investors in the energy sector see social spending as an operational burden that reduces company profitability. Governance disclosure has a significant negative effect on firm value, Governance disclosure has a significantly negative impact on firm value, which is because broader governance disclosure might be read by the market as a signal of fundamental weakness rather than strength due to the obligation to meet the minimum GCG standards set by the Financial Services Authority (OJK). These findings imply that compliance driven ESG disclosure has not yet been able to create market recognized added value in Indonesia's energy sector.